Cost and returns of groundnut crop in Andhra Pradesh: Cost and returns of groundnut crop in Andhra Pradesh - PERKA SHIVA KUMAR (Journal of Oilseeds Research, 2020)
The cost of cultivation data of Groundnut at Triennium Ending 2016-17 in Andhra Pradesh state reveals that the value of main product (`51003) of groundnut is lesser than the total cost of cultivation (`58588). Operational costs are 69% and fixed costs are 31% in total cost, among which human labour cost is highest (28.53%) followed by seed cost (17.21%), net returns are `15690 at cost A2, and negative (`-7585) at cost C2, which reveals that the farmers income is negative by considering own labour costs. Replacing human labour with low cost machines, development of some more HYV by the researchers, adoption of best management practices by the farmers, raise of MSP by the Government to meet the total expenditure are the suggestions that arise from the study.